2017
DOI: 10.3138/jvme.1016-163
|View full text |Cite
|
Sign up to set email alerts
|

Development of Veterinary Anesthesia Simulations for Pre-Clinical Training: Design, Implementation, and Evaluation Based on Student Perspectives

Abstract: Anesthesia simulations have been used in pre-clinical medical training for decades to help learners gain confidence and expertise in an operating room environment without danger to a live patient. The authors describe a veterinary anesthesia simulation environment (VASE) with anesthesia scenarios developed to provide a re-creation of a veterinarian's task environment while performing anesthesia. The VASE uses advanced computer technology with simulator inputs provided from standard monitoring equipment in comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies have shown that pairing sounds from electronic stethoscopes, digitally or Animals 2024, 14, 1341 3 of 19 in real-time, with phonographs assists with the identification of heart sounds to a greater degree than using conventional stethoscopes [13,16]. Integration of multidimensional teaching tools also improves animal health and well-being, as the students are better prepared during live animal interactions [1,17,18]. Hence an audio-visual equine cardiac auscultation resource was developed for veterinary students at UQ to integrate theoretical and practical content (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that pairing sounds from electronic stethoscopes, digitally or Animals 2024, 14, 1341 3 of 19 in real-time, with phonographs assists with the identification of heart sounds to a greater degree than using conventional stethoscopes [13,16]. Integration of multidimensional teaching tools also improves animal health and well-being, as the students are better prepared during live animal interactions [1,17,18]. Hence an audio-visual equine cardiac auscultation resource was developed for veterinary students at UQ to integrate theoretical and practical content (Figure 1).…”
Section: Introductionmentioning
confidence: 99%